CDKN2B Polymorphism Is Associated with Primary Open-Angle Glaucoma (POAG) in the Afro-Caribbean Population of Barbados, West Indies - Cao, Dan; Jiao, Xiaodong; Liu, Xing; Hennis, Anselm; Leske, M. Cristina; Nemesure, Barbara; Hejtmancik, J. Fielding (PLOS ONE, 2012)
The purpose of this study was to confirm previously reported associations of common variants in or near CDC7/TGFBR3, ZP4, SRBD1, ELOVL5, CAV1/CAV2, TLR4, CDKN2B, CDKN2B-AS1, ATOH7, PLXDC2, TMTC2, SIX1, and CARD10, with primary open angle glaucoma (POAG) in the Afro-Caribbean population of Barbados, West Indies. A total of 437 unrelated subjects from the Barbados Family Study of Open Angle Glaucoma (BFSG), including 272 with POAG and 165 unaffected individuals were included in this study. Eighteen SNPs were genotyped by using the multiplex SNaPshot method. Allelic, genotypic and model-based (dominant, recessive, and additive) associations of the SNPs with POAG were analyzed using Chi-squared tests and logistic regression. SNP rs1063192 (near CDKN2B) was found to be significantly associated with POAG (allelic P = 0.0008, genotypic P = 0.0029), and the minor allele C of rs1063192 was protective against POAG (OR = 0.39; 95%CI = 0.22−0.69). Suggestive association was also noted for rs7916697 (near ATHO7, allelic P = 0.0096, genotypic P = 0.01) with the minor allele being protective (OR = 0.67; 95% CI = 0.50−0.91), although this finding did not withstand correction for multiple testing. However, a significant interactive effect on POAG risk was identified between rs1063192 and rs7916697 (P-interaction = 2.80×10−5). Individuals with the rs1063192 protective genotype CC or CT and also rs7916697 genotypes GG or GA show a significantly decreased risk of POAG (OR = 0.17, 95%CI: 0.07−0.41). Our study confirms the significant association between SNP rs1063192 (CDKN2B, previously shown to influence vertical cup-to-disc ratio and POAG at 9p21) and POAG in the Afro-Caribbean population of Barbados. The minor allele of rs1063192 interacts with that of rs7916697 (ATOH7)) to reduce POAG risk. Our results also suggest that rs1063912 is a common protective variant for POAG in populations of African as well as European descent.